ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS KEDUNGDORO - Yuni Rachmawati; Achmad Daengs GS; Edo Galih Permadi (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Patient satisfaction is the result of the patient's assessment of health services by comparing what is expected with what he receives. Consumer demands for the quality of puskesmas services require a change in customer-oriented services by prioritizing service quality. This is to increase patient satisfaction with health services. The purpose of this study was to determine the effect of service quality on patient satisfaction at the Kedungdoro Health Center. This study is a quantitative study with a cross-sectional study design and survey method. The study population was all patients in November as many as 500 patients. The research sample was obtained using the Lwanga & Lemeshow formula as many as 180 patients and taken by the accidental sampling method. The research data were collected using a questionnaire and the data were analyzed using Multiple Linear Regression.The results showed that the results of the t-test of service quality variables in the formof physical evidence, reliability, responsiveness, assurance and empathy partially have a significant positive effect on the patient satisfaction variable. In addition, the F test showed that all service quality variables simultaneously or simultaneously had a significant effect on patient satisfaction. Variables of service quality that need to be evaluated for follow-up to increase patient satisfaction are elements of physical evidence and empathy..